2019
DOI: 10.1002/dev.21928
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptors and the ontogeny of post‐shock and retention freezing during contextual fear conditioning

Abstract: The ontogeny and NMDA‐receptor (NMDAR) mechanisms of context conditioning were examined during standard contextual fear conditioning (sCFC) – involving context and context‐shock learning in the same trial – as a comparison with our previous reports on the Context Preexposure Facilitation Effect (CPFE), which separates these two types of learning by 24 hr. In Experiment 1, systemic administration of the NMDAR antagonist, MK‐801, prior to conditioning disrupted retention but not post‐shock freezing during sCFC i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Post-shock freezing after a 5-min pre-exposure-to-training interval was lower than after a 0-min interval (Experiment 1B) and adding an additional 5-min interval between training and test reduced freezing even further so that it was no longer significantly (p > .077) above control levels (Experiment 1C). Finally, the present results support, and extend to the CPFE, previous findings that pre-weanling rats trained in standard contextual fear conditioning show acquisition (post-shock freezing) but not 24-hr retention of freezing behavior (Miller, Heroux, & Stanton, 2020;Rudy & Morledge, 1994). The level of post-shock freezing in the present study was much lower than what we and Rudy and Morledge (1994) found when 2-3 min of context exposure precedes shock.…”
Section: Discussionsupporting
confidence: 90%
“…Post-shock freezing after a 5-min pre-exposure-to-training interval was lower than after a 0-min interval (Experiment 1B) and adding an additional 5-min interval between training and test reduced freezing even further so that it was no longer significantly (p > .077) above control levels (Experiment 1C). Finally, the present results support, and extend to the CPFE, previous findings that pre-weanling rats trained in standard contextual fear conditioning show acquisition (post-shock freezing) but not 24-hr retention of freezing behavior (Miller, Heroux, & Stanton, 2020;Rudy & Morledge, 1994). The level of post-shock freezing in the present study was much lower than what we and Rudy and Morledge (1994) found when 2-3 min of context exposure precedes shock.…”
Section: Discussionsupporting
confidence: 90%
“…To test the role of α5-GABA A Rs expressed on interneurons and pyramidal neurons in etomidate’s suppression of hippocampus-dependent memory, we employed the Context Preexposure Facilitation Effect (CPFE) learning paradigm (Fig. 2a) – a variant of contextual fear conditioning that separates the contextual learning and aversive phases of conditioning 39, 40, 41, 42 . This paradigm takes advantage of the “immediate shock deficit” 43 , wherein mice that are shocked immediately after they are placed in a novel context fail to associate the context and shock, whereas mice that were pre-exposed to the context on the preceding day recall the context rapidly and successfully associate it with the shock 44, 45 .…”
Section: Resultsmentioning
confidence: 99%
“…We used a preexposure-dependent contextual fear conditioning paradigm adapted from Cushman et al, 2012 108 . This paradigm, which is often referred to in the literature as the Context Preexposure Facilitation Effect (CPFE) paradigm 40, 41, 42 takes advantage of the so-called “immediate shock deficit” 39, 43 , wherein animals that are shocked immediately (within several seconds) upon entry into a novel environment do not freeze on subsequent re-exposure, whereas mice that had been exposed on a prior day do exhibit a freezing response. The proposed explanation is that preexposed mice establish a hippocampus-dependent representation of the environment (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…In adulthood, chronic stress increases LTP formation in the BLA, which elicits the long-term consolidation of fear memories in male rats (Suvrathan et al, 2014). Activation of developmentally regulated glutamatergic NMDARs (Lopez de Armentia and Sah, 2003) critically mediates changes in synaptic plasticity and fear learning (Dalton et al, 2012;Miller et al, 2020). All three major NMDAR subunits (GluN1, GluN2A, and GluN2B) are expressed in the juvenile BLA (Delaney et al, 2013), but the effect of ELS on their expression and contribution to synaptic plasticity at this age are unknown.…”
Section: Introductionmentioning
confidence: 99%